Inovação, competências e recursos humanos: uma articulação possível? Estudo em organizações brasileiras e portuguesas - Glauciene Silva Martins (2013)
The assess the relationship between human resources, innovation, and competencies dimensions, identifying decisive actions for the creation, deployment and maintenance of organizational routines that contribute to innovation processes within companies. Given the complexity of these issues, the solution proposed led to the construction of an analytical framework of the relevant variables. The selection of the variables was based on the relevant theory and on the practice, from the perspective of managers that leading to clarify the relationship between the dimensions analyzed. The methodological strategy adopted was the case study, and data collection of primary information was based on semi-structured interviews with managers from eleven companies (five are located in Portugal and six in Brazil). The main results can be split in two forms: a) theoretical development of an argument which considers the social construction of innovation from the perspective of business management, covering elements of evolutionary economics, the notion of competencies and contemporary approach of human resources; b) practice the presentation of actions and perceptions of the actors of innovation within companies. Thus, this work generates benefits for future studies aimed at adding information and research tools in an attempt to improve the explanatory and interpretative ability of those who study and practice innovation in enterprises.